GAMBARAN TINGKAT PENGETAHUAN MASYARAKAT TENTANG SWAMEDIKASI OBAT ANALGESIK DI DUSUN PONDOK BUAK - NUR OKTAVIANI (GANEC SWARA, 2024)
Self-medication is the behavior of self-administering drugs based on a diagnosis of experienced symptoms. As many as 103,860 or 35.2% out of 294,959 households store drugs for self-medication, and the most commonly experienced complaint leading to self-medication is pain. Pain can become a problem if it is not promptly treated, leading to prolonged illness and potential harm to the individual. The aim of this research is to describe the public's knowledge level regarding self-medication of analgesic drugs in Pondok Buak village. This research is quantitative descriptive. This study's sample comprises of 134 people from the community who had self-medicate with analgesic medicines and satisfied the inclusion and exclusion criteria. Purposive sampling was employed for sampling. Furthermore, the instrument used in this study was a questionnaire with 11 questions about the level of knowledge of analgesic drug self-medication, which was classified as good (75%-100%), sufficient (56%-75%), and insufficient (56%). Univariate analysis was used to analyse the data. According to the findings, 55% of respondents had a solid knowledge of self-medication, 19% had an adequate comprehension, and 26% showed an insufficient understanding. Finally, with 74 respondents (55%), the description of the public's awareness level regarding self-medication of analgesic medications in Pondok Buak Hamlet is in the good category